KAMPANYE KOMUNIKASI KESEHATAN KEPADA PASIEN LANSIA DAN ANAK DI RUMAH SINGGAH PEDULI JAKARTA PUSAT - Wulan Purnama Sari; Audrey Sugito; Alexandra Virginia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Care Shelter in Central Jakarta Branch is a temporary shelter for patients who come from outside the city who have financial problems in terms of housing. However, there is only one administrator at the Care Shelter in Central Jakarta Branch, while the number of patients there is 9, consisting of 6 adult patients and 3 pediatric patients. Patients who stop by are patients who come from outside the city or areas who are having problems paying for a place to stay during the treatment period. This causes limitations on the costs of daily living, such as electricity bills and the basic needs of patients and caregivers. This limitation of funds is due to the absence of permanent donors for the Central Jakarta Branch of Care Shelter. Based on the results of observations and interviews with the Chief Coordinator of the Care Shelter Board and representatives of the patient companions, the main needs of the Care Shelter at the Central Jakarta Branch at this time are material needs. These needs include children's milk and adult milk, pampers for children and adults, vitamins, equipment, and household supplies. Apart from that, the problem in terms of material is the low understanding of how to maintain health, especially during a pandemic like that is also an obstacle faced by partners. Responding to this limitation, the PKM team held a health communication campaign for elderly patients and children at the Care Shelter, Central Jakarta Branch. The implementation method is a Health communication campaign by donating material and conducting discussions related to Health and simple ways that can be done to maintain health. The results obtained through this activity are the establishment of cooperation with partners and also assist partners in carrying out their duties, both in terms of material and literacy regarding health.